SISTEM PENDUKUNG KEPUTUSAN CERDAS KESESUAIAN LAHAN DENGAN JENIS TANAMAN PANGAN: STUDI KASUS KABUPATEN SIKKA - Yanter Wilve Baly Woda, Irman Hermadi, dan Marimin (Jurnal Teknologi Industri Pertanian, 2019)
Sikka District is an area with a dry tropical climate. Most of the plants especially food crops in Sikka District depend on rainfall. The lack of rain coupled with the weather anomalies occurring in Sikka District make Sikka District categorised in the area threatened by food insecurity.  Food crop cultivation often experiences obstacles, one of which is in determining the suitability of agricultural land for the advancement of certain food crops because the productivity of food crops depends on the quality of the area used. Therefore, this study aimed to develop a smart decision support system to determine land suitability with food crops. This study used a fuzzy analytic hierarchy process to determine the value of alternatives based on parameters that affect the relevance of the land with the type of food crop.  The results showed that corn food crops were the best alternative crop with a value of 0.339 of the three alternative food crops studied and then use the method fuzzy inference system to calculate the amount of land suitability. Kopong Village and Geliting Village were the best villages with land suitability values 81.Keywords: fuzzy analytic hierarchy process, fuzzy inference system, intelligent decision support systems, land suitability